Isolation and Biodegradation Capabilities of Native Fungi of Sanganer Region of Jaipur - Bishnoi, Om Prakash (International Journal of Pharmaceutical & Biological Archive, 2017)
The removal of the polluting dyes is an important problem, particularly for small scale industries where working conditions and economic status do not allow them to treat their waste water before disposal and they have no choice other than dumping all effluent into the main stream of water resources. Microbial declourisation and degradation is an environment friendly and cost competitive alternative to chemical decomposition processes (Verma and Madamwar, 2003). In the present study, we focused our attention on the screening of dye decolorizing fungi isolated from the contaminated soil and water samples from Sanganer and the extent of declourisation of synthetic dyes by these isolated fungi.